2020
DOI: 10.1167/jov.20.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Intra-saccadic motion streaks as cues to linking object locations across saccades

Abstract: When visual objects shift rapidly across the retina, they produce motion blur. Intra-saccadic visual signals, caused incessantly by our own saccades, are thought to be eliminated at early stages of visual processing. Here we investigate whether they are still available to the visual system and could-in principle-be used as cues for localizing objects as they change locations on the retina. Using a high-speed projection system, we developed a trans-saccadic identification task in which brief but continuous intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 80 publications
(226 reference statements)
2
52
0
Order By: Relevance
“…Furthermore, we not only showed that the effect of intra-saccadic object motion is orthogonal to the effect of primary saccade landing positions (cf. Hollingworth et al, 2008), but also provided evidence for the benefit of effective temporal integration when stimulus orientations were aligned with their retinal motion trajectories -a typical signature of motion streaks (Schweitzer & Rolfs, 2020). In other words, the more effectively the combined movement of eye and target in a given trial generated a motion streak, the more often did a secondary saccade go to the target.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, we not only showed that the effect of intra-saccadic object motion is orthogonal to the effect of primary saccade landing positions (cf. Hollingworth et al, 2008), but also provided evidence for the benefit of effective temporal integration when stimulus orientations were aligned with their retinal motion trajectories -a typical signature of motion streaks (Schweitzer & Rolfs, 2020). In other words, the more effectively the combined movement of eye and target in a given trial generated a motion streak, the more often did a secondary saccade go to the target.…”
Section: Discussionmentioning
confidence: 99%
“…Most experiments thus far, in fact, were built on the premise that "vision is suppressed, creating a gap in perceptual input" (Richard et al, 2008, p. 66) and "people are virtually blind" (Hollingworth et al, 2008, p. 163) during saccades. In contrast to this premise, we have recently shown that observers can use intra-saccadic motion streaks to tell pre-saccadic objects from identical distractors upon saccade landing (Schweitzer & Rolfs, 2020). The crucial question -if intra-saccadic streaks could be used to establish object correspondence across saccades -remains unanswered, however.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations